1973
DOI: 10.1071/bi9731409
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Cold Shock and Freeze-Thawing on Release of Phospholipids by Ram, Bull, and Boar Spermatozoa

Abstract: The effects of cold shock and freeze-thawing on the release of total phospholipid phosphorus and of specific phospholipids from ram, bull, and boar spermatozoa are examined. Species differences are apparent, both in the absolute amount of total phospholipids released and in the conditions required to effect a loss of individual phospholipids. The phosphoglycerides most affected by the temperature treatment are choline plasmalogen, phosphatidyl choline, and phosphat idyl ethanolamine. The loss of phospholipids … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

1975
1975
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(25 citation statements)
references
References 31 publications
1
24
0
Order By: Relevance
“…Membrane destabilization occurs when the membrane undergoes the phase transition, from the fluid phase to the gel phase, as temperature is decreased. During this phase transition, phospholipids are lost from the plasma membrane leading to increased membrane permeability, membrane disruption, and cell death (Darin-Bennett et al, 1973;Watson, 1981). If the temperature at which the membrane lipid phase transition occurs could be lowered, or if the membrane phase transition could be eliminated completely, membranes would remain fluid at low temperatures and the damage that occur to membranes may be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Membrane destabilization occurs when the membrane undergoes the phase transition, from the fluid phase to the gel phase, as temperature is decreased. During this phase transition, phospholipids are lost from the plasma membrane leading to increased membrane permeability, membrane disruption, and cell death (Darin-Bennett et al, 1973;Watson, 1981). If the temperature at which the membrane lipid phase transition occurs could be lowered, or if the membrane phase transition could be eliminated completely, membranes would remain fluid at low temperatures and the damage that occur to membranes may be reduced.…”
Section: Introductionmentioning
confidence: 99%
“…Healey, 1969;Kann & Hollande, 1972;Yasuda & Tanimura, 1974;Larsson & Einarsson, 1975). Such membrane damage is paralleled by loss of lipid during cold-shock or freezing-thawing (Hartree & Mann, 1959;Pickett & Komarek, 1967;Darin-Bennett et ai, 1973 (Darin-Bennett et al, 1973), and this may be related to the decreased relative incorporation of stearic acid into phosphatidyl choline and of both stearic and palmitic acids into phospholipids in general. Although not significant the apparent decline in incorporation of the fatty acids into the fraction containing phosphatidyl serine may be related to the protection by phosphatidyl serine of boar spermatozoa against cold shock (Butler & Roberts, 1975 (Watson, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…That membrane damage occurs during storage has been inferred from the loss of intracellular constituents (Mann, 1964;Graham & Pace, 1967; Darin-Bennett, Poulos & White, 1973), from the increased membrane permeability to stains (Easley, Mayer & Bogart, 1942;Mann, 1964), and from morphological changes (e.g. Healey, 1969;Kann & Hollande, 1972;Yasuda & Tanimura, 1974;Larsson & Einarsson, 1975).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies also observed lower cholesterol content after freezing-thawing of porcine (Cerolini et al, 2001) and buffalo (Kadirvel et al, 2009) spermatozoa. Sperm membranes are known to release phospholipids into surrounding medium during cold shock (Darin-Bennett et al, 1973). Release of cholesterol from the membrane plane, a probable consequence of peroxidative damage to membrane lipids, could lead to the premature capacitation of cryopreserved bovine spermatozoa (Cormier et al, 1997).…”
Section: Cholesterol Effluxmentioning
confidence: 99%